Neopentecostalismo difuso: movimientos evangélicos en Tijuana - Jaimes Martínez, Ramiro; Montalvo González, Alethia Alejandra (El Colegio de México, 2018)
The purpose of this study is to reflect on the usefulness of categories such as “Pentecostalism,” “Charismatics,” and “Neo-Pentecostalism,” in order to study religious change in Mexico. To achieve this, we analyze both the trajectory and the impact of two evangelical movements in the religious field of Tijuana, specifically during their formative years. For this, one needs to ask to what extent it is possible to assume that Neo-Pentecostalism constitutes a wave of Pentecostalism that can be explained based on liturgy and doctrinal criteria so extensive as the theology of prosperity and the gifts of the spirit. Based on the preceding, the category of “Neo-Pentecostalism” is problematized and proposed to be used exclusively for churches which arose from the Charismatic movement within Pentecostal denominations.